2014
DOI: 10.1007/s10120-014-0396-5
|View full text |Cite
|
Sign up to set email alerts
|

Gene polymorphisms in the ornithine decarboxylase–polyamine pathway modify gastric cancer risk by interaction with isoflavone concentrations

Abstract: Background The study aimed to examine the association between genes encoding molecules in the ornithine decarboxylase (ODC)-polyamine pathway (ODC1, AMD1, NQO1, NOS2A, and OAZ2) and gastric cancer risk and whether the gene-phytoestrogen interaction modifies gastric cancer risk. Methods Among 76 gastric cancer cases and their 1:4 matched controls within the Korean Multi-center Cancer Cohort, a total of 30 SNPs in five genes involved in the ODC pathway were primarily analyzed. The second-stage genotyping in 388 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…It has been found that elevated polyamine level is closely related to the increased GC risk . The ODC‐polyamine pathway may increase the growth of GC cells through controlling host DNA damage and immune reaction . It indicates that GC cells may use arginine–ornithine–polyamine pathway to synthesis polyamines to promote the proliferation of carcinoma cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been found that elevated polyamine level is closely related to the increased GC risk . The ODC‐polyamine pathway may increase the growth of GC cells through controlling host DNA damage and immune reaction . It indicates that GC cells may use arginine–ornithine–polyamine pathway to synthesis polyamines to promote the proliferation of carcinoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Green blocks represent the five amino acids in the regression diagnosis model. immune reaction (42). It indicates that GC cells may use arginine-ornithine-polyamine pathway to synthesis polyamines to promote the proliferation of carcinoma cells.…”
Section: The Differences Of Amino Acids Between Gc and Gu Groupsmentioning
confidence: 99%
“…As an endogenous ODC-activity antagonist, the antizyme 2 (OAZ2) expression is expected to be downregulated during cancer progression. Indeed, a dramatic decrease in the expression of OAZ2 has been reported in gastric cancer [ 51 ] and neuroblastoma [ 52 ], and high levels of OAZ2 expression are positively correlated with increased survival rate and favorable clinical prognosis. In this context, we reason that the chemosensitivity-promoting effects of OAZ2 may exhibit through antagonizing ODC activity.…”
Section: Discussionmentioning
confidence: 99%
“…Xiao et al [ 38 ] found that PYCR1, a key enzyme in intracellular proline synthesis, is highly expressed in GC, which induces cancer progression by increasing tumor proliferation and reaction to metabolic stress[ 38 ]. Another metabolic gene, known as the ODC1 , has been reported to contribute to the risk of GC by regulating the biosynthesis of ornithine decarboxylase polyamines or by the interaction between isoflavones and NQO1, OAZ2, and AMD1[ 39 ]. In summary, all these studies emphasize the tight connection between metabolic genes and the formation of GC, indicating that changes in specific metabolic pathways may influence the occurrence of GC.…”
Section: Metabolic Genes Involved In the Development Of Gcmentioning
confidence: 99%